Nerve conduction study of ulnar nerve in volleyball players - Özbek, A.; Bamac, B.; Budak, F.; Yenigün, N.; Colak, T. (Scandinavian Journal of Medicine & Science in Sports, 2006)
Ulnar neuropathy at the elbow is a common disorder seen in the throwing athlete. The purpose of our study was to determine whether asymptomatic physically active volleyball players and non-actives demonstrate distinct differences in nerve conduction of the ulnar nerve at the elbow. Nerve conduction studies were performed on both arms of 24 male volleyball players and 24 male non-actives. Nerve conduction velocity at the above to below elbow segment of the ulnar motor nerve were slower in the volleyball players compared with controls and their non-dominant arms. There were no statistical differences in latencies and conduction velocity of the ulnar nerve on the forearm, both in volleyball players and in the controls. In the evoked responses of the ulnar nerve, the amplitude was the same as corresponding normal values in both sensory nerve and muscle action potentials. We conclude that abnormal ulnar (motor) nerve conduction at the elbow segment may suggest a subclinical entrapment neuropathy as a result of strenuous elbow movements in volleyball players.